Pharella Acutidens Clams Population Dynamic in Mangrove Ekosistem, Cempi Bay,Woja District, Dompu Regency, West Nusa Tenggara - Dermawan, Awan; Abidin, Zaenal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study examines the growth of the Pharella acutidens clam in mangrove ecosystem of Cempi Bay, which has a habit of living in the substrate with a vertical shell position. These clams emit siphons when the hole they live is waterlogged to obtain food. Field observations showed that the depth of the Pharella acutidens hole was strongly influenced by the tide. During high tide, the clam moves close to the surface up to 10 cm from the substrate, while during low tide, the clam can bury itself to a maximum depth of 70 cm and a minimum of 25 cm. The minimum shell length recorded was 4.90 cm, while the maximum length of Pharella acutidens clams was 9.30 cm. the highest L∞ (9,71) and K (0.45) is found in locations that are densely vegetated, the lowest L∞ (7,88) and K (0.38) is found in low vegetated locations. There is something interesting because the low-vegetated location and higher disturbance has a relatively high recruitment value.